The Impact of Carbon Tax Application on the Economy and Environment of Indonesia (European Journal of Marketing and Economics, 2026)
As the most efficient market with a mitigation instrument basis, carbon tax is highly recommended by economists and international organizations. This paper examines the impact of implementing carbon tax policy on value of change in GDP, GDP Quantity Index, Government Household Demand, Private Household Demand, and CO2 emission effects in Indonesia by using the dynamic energy Computable General Equilibrium (CGE) model.  This study used GTAP-E that was part of GTAP 9 in 2011. GTAP-E consists of 140 countries and 57 sectors aggregated into eleven regions and eight sectors. There were three scenarios of carbon tax used in this paper that were China, Singapore, and India. The result shows that both GDP and GDP index have a negative impact due to the carbon tax of US $20/tCO2, US$ 10/tCO2, and US $1.60/t CO2. The greater the application of the carbon tax is, the greater the decrease of values of GDP, Government Household Demand, Private Household Demand towards carbon tax policies in Indonesia are. The negative impact of carbon tax is greater for the Private Household Demand that is indicated by all commodities except crude oil has decreasing demand from baseline scenario (no tax). While in the Government Household Demand, agriculture sector, crude oil, refined oil product, and other industries, carbon tax has a positive impact. In the environmental facet, if the carbon tax in Indonesia is implemented in accordance with the above simulation, then it appears that carbon tax can reduce emissions of CO2.
Keywords: Carbon Tax, GDP, Government Household Demand, Private Household Demand, CO2 Emissions, GTAP-E